2015
DOI: 10.1111/ejh.12644
|View full text |Cite
|
Sign up to set email alerts
|

Patients with multiple myeloma have excellent long‐term outcomes after recovery from dialysis‐dependent acute kidney injury

Abstract: In this series, the large majority of patients with MM and dialysis-dependent AKI secondary to myeloma cast nephropathy who recovered independent renal function had no requirement for further dialysis. Survival following recovery of renal function is good, and early variables are independently associated with survival and future renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…There are significant health and social implications associated with long term RRT, including increased frequency of infection, reduced quality of life and financial pressures (Berman et al, 2004). Unlike cast nephropathy, MGRS patients do not appear to demonstrate the same ability to recover renal function (Yadav et al, 2016), with three of the four patients who were on RRT at the time of diagnosis remaining on RRT for the duration of the study. Similar to multiple myeloma with renal impairment, progression to RRT and renal failure limits chemotherapy treatment options in the event of disease relapse.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…There are significant health and social implications associated with long term RRT, including increased frequency of infection, reduced quality of life and financial pressures (Berman et al, 2004). Unlike cast nephropathy, MGRS patients do not appear to demonstrate the same ability to recover renal function (Yadav et al, 2016), with three of the four patients who were on RRT at the time of diagnosis remaining on RRT for the duration of the study. Similar to multiple myeloma with renal impairment, progression to RRT and renal failure limits chemotherapy treatment options in the event of disease relapse.…”
Section: Discussionmentioning
confidence: 96%
“…Depth of haematological response appears to improve renal surviva (RS) (Rajkumar et al , ), but limited numbers of patients received novel anti‐plasma cell agents, such as thalidomide and bortezomib in these series. MGRS lesions, cast nephropathy and renal immunoglobulin light chain (AL) Amyloidosis have previously been reported and were therefore excluded from this retrospective study (Wechalekar et al , ; Yadav et al , ).…”
mentioning
confidence: 99%
“…It is important to consider for future clinical studies that renal insufficiency could be a contraindication for usage of PAA in MM patients. Renal impairment is a common complication of MM (50%) and up to 5% require dialysis (Yadav et al, 2016a, Yadav et al, 2016b). The clinical toxicity is probably from oxalate, an end-product of ascorbate metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Yadav et al shown that the median time to death in these patients was 5.1 months [31]. It is important to highlight that an early initiation of hemodialysis and prompt hemodialysis may improve the outcome [30].…”
Section: Discussionmentioning
confidence: 96%
“…In a single-center study, renal recovery was associated with effective treatment of MM and a sustained reduction in the concentration of the involved FLC clone. The majority of patients who recover renal function have no further need for dialysis [31]. It has been described that the median overall survival in people who recovered renal function was 62.4 [32] -64.1 [31] months.…”
Section: Discussionmentioning
confidence: 99%